Chemical Properties, Crystallinity and Morphological of Oil Palm Trunk Parenchyma and Vascular Bundle - Junidah, Lamaming; Rokiah, Hashim; Cheu Peng, Leh; Tomoko, Sugimoto; Othman, Sulaiman (IRED, 2015)
Parenchyma and vascular bundle of oil palm trunk were segregated manually and were evaluated for their holocellulose, α-cellulose, hemicelluloses, lignin and starch content accordingly. The functional groups, crystallinity and morphological characteristics were also studied using FTIR, XRD and scanning electron microscopy respectively. The results showed that oil palm trunks were found to be rich in the vascular bundle rather than in parenchyma. It was shown that the vascular bundle had a higher amount of α-cellulose compared to parenchyma which had a higher amount of lignin, extractives and starch. The XRD analyses reveal that the vascular bundle of oil palm trunk contain a high percentage of crystallinity index compared to parenchyma.